Diversities in Diversity: Exploring Moroccan Migrants' Livelihood in Genoa - Roberto Alzetta (Fondazione Eni Enrico Mattei (FEEM), 2006)
It is a largely accepted idea that complexity and recent global phenomena have generated a multi-layered diversification process in Western societies. Migration phenomena are largely responsible for this process both in receiving European societies as well as in original sending countries. Migration has been and continues to be a ubiquitous human experience. Yet, while this fact has aided the understanding of the world as something other than a mosaic of distinct cultural spaces with clearly demarcated borders, it has not decreased the incomprehension, fear and suspicion with which non European migrants are often greeted within the industrialised cities of Europe. This article deals with one aspect of this process that seems to be quite underestimated in media, public opinion and academia. It is the idea that ethnicity can be approached, explored and investigated as a heterogeneous and multi-faced form of diversity itself. This is what can be defined as diversities within diversity . Departing from the presentation of an empirical research in Genoa it will be possible to analyse these phenomena at two different levels: namely, in terms of methods and methodology. By focusing on the idea of livelihood and employing an approach based on Tracing techniques, different ways of acting and being Moroccan migrants in Genoa will be revealed, presented and discussed. This method newly integrates both quantitative and qualitative information. It will allow us to analyse the experience of livelihood in a way that will reveal the simultaneous existence of many underlying different invisible and unconscious social constructions as well as visible concrete and conscious expressions of everyday life. Disclosing how the same people in the same local context produce different adaptive strategies and lifestyles will lead to outline a potential conceptual methodological framework of reference based on an open/close principle. In this case ideas of openness and closeness will be assumed in a dialectical double-faced process. It is not only a matter of how systems can be defined open or closed by themselves, but also how the encounter and interplay of many different systems generation of diversity - establish the conditions and limits within which different individuals can reproduce their culture as social actors- production of diversities. After having discussed the methodological implications of this approach it will be possible to draw some final theoretical considerations. If we believe that new ways of investigating social phenomena are a determinant in the way we describe, analyze, explain and understand their complexity, we should recognize that not only theory might generate and define what we call social reality but also vice-versa. Approaching the world out there in new ways might result in rethinking and adjusting the conceptual taxonomies that drive social scholars in their search for gaining and catching social reality. This principle becomes crucial if we want social sciences to be heuristically oriented, in other words if we want to develop the capacity to hand back positive analytical readings and comparisons of social phenomena as well as useful recommendations for policy makers.
Keywords: F22; O15; J15; O18; 330; Migration; Italy; Morocco; Methodology; Tracing; Open/close Model